2008
DOI: 10.1111/j.1432-0436.2007.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of monoamine oxidase A promotes secretory differentiation in basal prostatic epithelial cells

Abstract: Monoamine oxidase A (MAO-A) expression is associated with high-grade prostate cancer. Immunohistochemistry showed that MAO-A is also expressed in the basal epithelial cells of normal prostate glands. Using cultured primary prostatic epithelial cells as a model, we showed that MAO-A prevents basal epithelial cells from differentiating into secretory cells. Under differentiationpromoting conditions, clorgyline, an irreversible MAO-A inhibitor, induced secretory cell-like morphology and repressed expression of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 48 publications
7
41
0
Order By: Relevance
“…We observed both increased MAOA expression and EMT in the same specimens of high-grade PCa, which, in line with our other results showing that MAOA can drive EMT (Figure 1), provides a molecular basis for the acquisition of a more aggressive phenotype in high-Gleason grade PCa. Our observation is consistent with previous studies showing that pharmacological inhibition of MAOA in PCa cells kept basal prostatic epithelial cells from differentiating into matured glandular structures by reorganizing cell structures and decreasing the expression of basal cytokeratins (9). In addition, a recent clinical survey assessing EMT marker levels in clinical samples with organ-confined PCa revealed that vimentin and TWIST1, among 13 other EMT markers, showed the most promising predictive potential for poor prognosis including biochemical recurrence (57).…”
Section: Figure 11supporting
confidence: 92%
See 1 more Smart Citation
“…We observed both increased MAOA expression and EMT in the same specimens of high-grade PCa, which, in line with our other results showing that MAOA can drive EMT (Figure 1), provides a molecular basis for the acquisition of a more aggressive phenotype in high-Gleason grade PCa. Our observation is consistent with previous studies showing that pharmacological inhibition of MAOA in PCa cells kept basal prostatic epithelial cells from differentiating into matured glandular structures by reorganizing cell structures and decreasing the expression of basal cytokeratins (9). In addition, a recent clinical survey assessing EMT marker levels in clinical samples with organ-confined PCa revealed that vimentin and TWIST1, among 13 other EMT markers, showed the most promising predictive potential for poor prognosis including biochemical recurrence (57).…”
Section: Figure 11supporting
confidence: 92%
“…Recently, a significant correlation was established between increased levels of MAOA expression and high Gleason grade or poorly differentiated human prostate tumors (7,8). MAOA is exclusively expressed in the epithelial cells of prostatic glands with relatively low levels in stromal counterparts (9). These observations collectively suggest that MAOA may function in an autocrine manner to regulate the proliferation and differentiation of prostatic epithelial cells.…”
Section: Introductionmentioning
confidence: 97%
“…By confocal imaging, some of them appear to have formed a hollow mound (data not shown). A recent study demonstrated that co-treatment of prostate basal cells with the monoamine oxidase A inhibitor clorgyline, 1,25-dihydroxyvitamin D 3 , all-trans retinoic acid and TGF-1 induced AR expression and loss of basal marker K14 (Zhao et al, 2008), suggesting that there might be alternative mechanisms to inducing prostate epithelial cell differentiation.In contrast to other published systems, we have demonstrated that our model can be utilized for biochemical and genetic manipulation. It is amenable to treatment with pharmacological inhibitors or siRNA to study signaling and biological pathways.…”
mentioning
confidence: 99%
“…Subsequent studies demonstrated that MAOA inhibits prostate cell differentiation (28), and the MAOA inhibitor clorgyline is capable of suppressing pro-oncogenic programs in prostate cancer cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…Task 15: Repeat Tasks 10-13 for two additional proteins (months [24][25][26][27][28][29][30][31][32][33][34]. Due to the failure of ELISA specificity, we evaluated the Luminex system for the utilization of single- Figure 4.…”
Section: Objective 1b Ihc Analysis/confirmation Of Protein Expressiomentioning
confidence: 99%